Políticas Culturais na Ibero-América - Brandão, Hanayana (Políticas Culturais em Revista, 2009)
RUBIM, Antonio Albino Canelas; BAYARDO, Rubens (Orgs.). Políticas Culturais na Ibero-América. Salvador: EDUFBA, 2008. 352 p.